Diseño de prensa hidráulica automática para 300 toneladas con dispositivo de extracción de rodamientos y mesa móvil (2016)
This project was a "design of press hydraulic automatic for 300 tons with device extraction of bearings and table mobile" seeking to optimize the operations of extraction of bearings and straightening of beams that are in the process of maintenance and manufacturing, improve the working conditions of the operator to decrease the risk of an accident at work, also seeks a greater performance and productivity in these processes that are performed in the FRC engineer S.A.S. company.